Two-Level Minimally Invasive Transforaminal Lumbar Interbody Fusion: Surgical Technique and Illustrative Cases. (5th September 2013) - Petteys, Rory J.; Rhee, Jay; Voyadzis, Jean-Marc
Abstract : Transforaminal lumbar interbody fusion (TLIF) is a common procedure performed by spine surgeons. The indications for TLIF include back pain and radiculopathy as a consequence of canal or foraminal stenosis, degenerative disc disease, spondylolisthesis, or deformity. Minimally invasive techniques (MIS) have proven to be effective for single-level TLIF and are associated with less blood loss, fewer wound complications and infections, faster recovery, and decreased hospital cost. To date, there is very little data on 2-level MIS TLIF. We present our technique for 2-level MIS TLIF with case illustrations and a review of the literature.